Evaluating effectiveness of small group information literacy instruction for Undergraduate Medical Education students using a pre‐ and post‐survey study design. (23rd March 2015) - McClurg, Caitlin; Powelson, Susan; Lang, Eddy; Aghajafari, Fariba; Edworthy, Steven
Abstract Background The Undergraduate Medical Education (UME) programme at the University of Calgary is a three‐year programme with a strong emphasis on small group learning. Objective The purpose of our study was to determine whether librarian led small group information literacy instruction, closely integrated with course content and faculty participation, but without a hands on component, was an effective means to convey EBM literacy skills. Method Five 15‐minute EBM information literacy sessions were delivered by three librarians to 12 practicing physician led small groups of 15 students. Students were asked to complete an online survey before and after the sessions. Data analysis was performed through simple descriptive statistics. Results A total of 144 of 160 students responded to the pre‐survey, and 112 students answered the post‐survey. Instruction in a small group environment without a mandatory hands on component had a positive impact on student's evidence‐based information literacy skills. Students were more likely to consult a librarian and had increased confidence in their abilities to search and find relevant information. Conclusion Our study demonstrates that student engagement and faculty involvement are effective tools for delivering information literacy skills when working with students in a small group setting outside of a computer classroom.